Batas Perlindungan Hukum Bagi Civilian Combatants dalam Perspektif Hukum Humaniter Internasional - Putu Fairnanda Sastra Devi; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The development of modern armed conflicts shows the increasing involvement of civilians in hostilities, which has given rise to the phenomenon of civilian combatants and created ambiguity in the classification of subjects in International Humanitarian Law. This study aims to analyze the legal status of civilians involved in armed conflicts and the limits of legal protection inherent to them. The research method used is normative juridical with a legislative and conceptual approach, through an analysis of international legal instruments and relevant doctrines. The results show that civilian combatants are not explicitly recognized in international humanitarian law, thus creating uncertainty in determining their legal status. Furthermore, protection for civilians is conditional and can be temporarily lost when individuals engage in direct participation in hostilities, with limits determined by the principles of distinction and proportionality. These findings confirm that the limits of legal protection are dynamic and depend on individual actions in conflict. The implications of this study indicate the need for strengthened legal interpretation and more consistent implementation to ensure legal certainty and protection for civilians in modern armed conflicts.